An Efficient One-Pot Synthesis of 3,5-Diaryl-4-bromopyrazoles by 1,3-Dipolar Cycloaddition of In Situ Generated Diazo Compounds and 1-Bromoalk-1-ynes - Sha, Qiang; Wei, Yunyang (Synthesis, 2013)
A simple, highly efficient, one-pot synthesis of 3,5-diaryl-4-bromopyrazoles via 1,3-dipolar cycloaddition of diazo compounds and alkynyl bromides has been developed. The diazo compounds and alkynyl bromides were generated in situ from tosylhydrazones and gem-dibromoalkenes, respectively. When ketone-derived hydrazones were used, 3,5-diaryl-4-bromo-3H-pyrazoles were obtained and the isomerization products 3,5-diaryl-4-bromo-1H-pyrazoles were formed when using aldehyde-derived hydrazones. The reaction system exhibited high regioselectivity and good functional group tolerance. Both electron-rich and electron-deficient substituents on the aromatic ring of the hydrazones or the gem-dibromoalkenes gave desired products in moderate to good yields (67–86%).
Keywords: cycloaddition; diazo compounds; hydrazones; pyrazoles; gem-dibromoalkenes